Histamine liberation and membrane fluidisation of mast cells exposed to the beta-adrenoceptor blocking drug propranolol - Nosál, R; Ondrias, K; Pecivová, J; Drábiková, K (Agents and actions, 1988)
Propranolol liberates histamine from isolated mast cells and decreases the uptake of extracellular histamine in a dose-dependent way. Histamine liberation due to propranolol is accompanied by calcium displacement from intracellular storage sites. The significant increase in membrane fluidity due to propranolol is temperature dependent. The perturbation of membranes is most probably the explanation of propranolol's interaction with isolated rat mast cells which results in altered histamine transportation.
Keywords: Calcium; Male; Rats, Inbred Strains; Mast Cells; vápník; techniky in vitro; uvolňování histaminu; Histamine Release; mužské pohlaví; inbrední kmeny potkanů; Propranolol; Histamine; krysa rodu Rattus; histamin; Animals; fluidita membrány; zvířata; mastocyty; Rats; propranolol; Membrane Fluidity; In Vitro Techniques